Inflation expectations in CESEE: The role of sentiment and experiences - Katharina Allinger; Fabio Rumler (Oesterreichische Nationalbank (OeNB), 2023)
This paper focuses on the formation of inflation expectations of consumers in 9 Central, Eastern and Southeastern European (CESEE) countries. Using data from the OeNB Euro Survey, a large cross-country consumer survey, we show that the difference between realized inflation and reported inflation expectations is considerably higher in CESEE countries than in 7 euro area countries. Moreover, we find that estimation results for the CESEE countries are in line with the existing literature on large Western economies: older, female and lower income respondents have relatively higher inflation expectations. Also, respondents with lower trust in institutions and a more pessimistic view regarding the economic outlook have substantially higher inflation expectations, as do those who were negatively financially affected by the COVID-19 pandemic or have experienced high inflation periods in the past. When interacting economic sentiment and experiences we find that differences in economic sentiment can partially explain the significant correlation between COVID-19 experiences and inflation expectations. Furthermore, respondents who remember high inflation in the past report a stronger effect of economic sentiment on inflation expectations than others.
Keywords: D12; D84; E31; E52; 330; inflation expectations; economic sentiment; CESEE; household survey